Association between COVID-19 and Seasonal Influenza Vaccines to Vaccine Hesitancy, Intolerance of Uncertainty and Mental Health - Maayan Shacham; Yaira Hamama-Raz; Menachem Ben-Ezra; Yafit Levin (Vaccines, 2023)
Vaccine hesitancy is a universal problem that is becoming more prevalent, ranging from partial acceptance to the complete refusal of various vaccines. The current study seeks to assess the relationship between vaccine hesitancy, intolerance of uncertainty, and mental health factors and those who were vaccinated against COVID-19 and seasonal influenza in comparison to those who did not vaccinate against both or decided to be vaccinated with only one of these vaccines. Employing a cross-sectional design, 1068 Israeli participants were recruited via social media (mainly Facebook) and Whatsapp and completed questionnaires assessing vaccine hesitancy, intolerance of uncertainty, and mental health factors. Our results revealed that previous history of neither COVID-19 nor seasonal influenza vaccination was associated with increased vaccine hesitancy. In addition, individuals who received either one vaccine or both claimed elevated levels of intolerance of uncertainty and reported elevated levels of mental health symptoms. Therefore, an association between vaccine hesitancy and intolerance of uncertainty and mental health symptoms is demonstrated. Future campaigns against vaccine hesitancy may focus on the intolerance of uncertainty in vaccine-hesitant individuals.